Allegory of Impunity in Vijay Malla’s Pattharko Katha - Rijal, Shiva (Journal of Innovation in Academia, 2024)
Written in 1971, the one-act play Pattharko Katha by Vijay Malla (1925-1999), staged by the student artists from Tribhuvan University, embodies the state of political helplessness that Nepalis had to go through right after the then King Mahendra Bir Bikram Shah Dev (1920-1972) dismissed the historically significant democratically elected government led by Prime Minister Bishweshwor prasad Koirala (1914-1982) in 1961. This paper aims to read the play as the political allegory of the period when the Rana rulers and their cronies were left unpunished, and most of the victims of the autocratic regime had no choice but to swallow the bitter pills. It points out that the action taken by the King as part of installing a partyless Panchayat regime did pave the way for the state of helplessness among people. Malla, someone who had played an active role in the 1950 historical revolution that had brought the Rana regime to its end, found himself serving the recently established Royal Nepal Academy in an important position during the partyless Panchayat regime. Malla’s Pattharko Katha employs political allegory by presenting the characters who find themselves turned into stone and realize the impossibility of taking revenge upon the culprit. This study concludes that the play allegorizes the pain and frustration of Nepalis bound to live through impunity rampant in Nepali society during the early years of the Panchayat regime.